Selection of sciatic nerve injury models: implications for pathogenesis and treatment - Zhou, Pinxi; Zhang, Ruhan; Xian, Liangmei; Ning, Le; Lu, Penghui; Liu, Qianyan; Liu, Mi (Frontiers in Neurology, 2025)
Sciatic nerve injury is one of the most frequent peripheral nerve injuries in the world. The loss of motor and sensory function, along with chronic pain caused by sciatic nerve injury, significantly impacts patients’ quality of life. However, there are numerous restrictions on in vitro studies on the regeneration and healing of sciatic nerve damage. In contrast, in vivo studies can more accurately mimic clinical pathology through a variety of experimental animal models and a variety of modeling methods. However, the selection of different models has its focus, so this paper reviews the selection of experimental animals, modeling methods, and common treatment protocols. The advantages and disadvantages of each species are discussed, and the modeling methods of five common sciatic nerve injury models, along with their characteristics and applications, are highlighted. Additionally, we briefly summarize the common treatments for sciatica and nerve injury. This review is of great significance for further exploring model selection, the mechanisms underlying sciatic nerve injury, and therapies for nerve regeneration and repair.